AIF inhibits tumor metastasis by protecting PTEN from oxidation - Shen, Shao-Ming (EMBO Rep, 2015)
Apoptosis-inducing factor (AIF) exerts dual roles on cell death and survival, but its substrates as a putative oxidoreductase and roles in tumorigenesis remain elusive. Here, we report that AIF physically interacts with and inhibits the oxidation of phosphatase and tensin homolog on chromosome ten (PTEN), a tumor suppressor susceptible for oxidation-mediated inactivation. More intriguingly, we also identify PTEN as a mitochondrial protein and the ectopic expression of mitochondrial targeting sequence-carrying PTEN almost completely inhibits Akt phosphorylation in PTEN-deficient cells. AIF knockdown causes oxidation-mediated inactivation of the lipid phosphatase activity of PTEN, with ensuing activation of Akt kinase, phosphorylation of the Akt substrate GSK-3β, and activation of β-catenin signaling in cancer cells. Through its effect on β-catenin signaling, AIF inhibits epithelial–mesenchymal transition (EMT) and metastasis of cancer cells in vitro and in orthotopically implanted xenografts. Accordingly, the expression of AIF is correlated with the survival of human patients with cancers of multiple origins. These results identify PTEN as the substrate of AIF oxidoreductase and reveal a novel function for AIF in controlling tumor metastasis.